Fondasi Teologis Moderasi Beragama Berdasarkan Lukas 10:25–37: Kajian Eksegetis tentang Orang Samaria yang Murah Hati - Sapta Baralaska Utama Siagian; Nini Adelina Tanamal (STTI Harvest Semarang, 2026)
Indonesia as a pluralistic society continues to face challenges in the form of intolerance, identity polarization, and weakening of social solidarity. In this context, religious moderation is an important framework to strengthen peaceful coexistence without sacrificing faith beliefs. This study aims to examine how Luke 10:25–37 can be read as a theological foundation for religious moderation through the figure of the Good Samaritan. This study uses a descriptive qualitative approach with a literature study design. Analysis is carried out through historical-grammatical exegetical methods, narrative analysis, and theological-contextual reflection. Primary data are in the form of the text of Luke 10:25–37, while secondary data comes from journal articles, books, and cutting-edge scholarly documents that discuss religious moderation, Jewish–Samaritan relations, compassion, hospitality, and public theology. The results show that the scribes' question of